Earmarks and Subcommittee Government in the U.S. Congress. (November 2015) - Clemens, Austin; Crespin, Michael; Finocchiaro, Charles J.
In recent years, considerable scholarly attention has focused on earmarks, the quintessential example of pork barrel politics. We assess the degree to which existing theories can explain the distribution of earmarks in the U.S. House of Representatives. First, drawing on informal interviews with individuals on Capitol Hill regarding the earmark process, we argue that assessing institutional and constituency-level factors that affect the earmark receipts of individual members requires examination at the level of the Appropriations subcommittees. Second, we demonstrate that both distributive and partisan theories of legislative organization are applicable to the distribution of earmarks. Finally, we present results indicating that contrary to the conventional wisdom, most subcommittees do not distribute pork based on electoral vulnerability. Rather, legislators' status in the appropriations process has the most influence. These findings offer insights into the path forward as debate continues over congressionally directed spending.